The impact of the Hudson’s Bay Company on the creation of Treaty Number Nine - Calverley, David (Ontario History, 2006)
In the summers of 1905/1906 the Dominion government entered into a treaty with the Cree and Ojibwa of northern Ontario. Known as Treaty Nine it encompassed a vast portion of the province. This treaty could not have been accomplished with the ease that it was without the assistance of the Hudson’s Bay Company. Acting in its own self-interest the HBC facilitated the government’s attempts to create a treaty. Understanding the HBC’s role in the treaty process highlights the continued importance of the Company in northern Canada, and its affect on treaty creation.